2023
DOI: 10.1039/d3cp01299a
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying methyl tunneling induced (de)coherence of nitroxides in glassy ortho-terphenyl at low temperatures

Abstract: The low-temperature Hahn echo decay signal of the pyrroline-based nitroxide H-mNOHex in ortho- terphenyl (OTP) shows two contributions on distinct time scales. Tunneling of the nitroxide’s methyl groups cause electron...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 64 publications
(134 reference statements)
2
20
0
Order By: Relevance
“…As a plausible explanation of these experimental results, we suggest that the low-temperature dynamics of methyl (and potentially amino) groups govern decoherence in photosynthetic proteins. This is in agreement with several experimental and theoretical studies on the model systems, where methyl group rotation, libration, and tunneling have been shown to substantially enhance decoherence at low temperatures. It is quite likely that similar factors also limit the coherence time in other photosynthetic RC proteins.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…As a plausible explanation of these experimental results, we suggest that the low-temperature dynamics of methyl (and potentially amino) groups govern decoherence in photosynthetic proteins. This is in agreement with several experimental and theoretical studies on the model systems, where methyl group rotation, libration, and tunneling have been shown to substantially enhance decoherence at low temperatures. It is quite likely that similar factors also limit the coherence time in other photosynthetic RC proteins.…”
Section: Introductionsupporting
confidence: 88%
“…Less intuitively, methyl groups can still enhance decoherence at low temperatures via tunneling, which is observed even at very low temperatures such as a few kelvin. 44,45,47,48,64,65 As a plausible explanation of our experimental results, we suggest that this low-temperature dynamics of methyl groups, and potentially similar dynamics involving amino groups, in protein microenvironments surrounding the spin-carrying donor/acceptor cofactors provides an additional mechanism for decoherence and leads to the short times observed here. Analysis of the crystal structure of PSI revealed that many methyl groups in the close surrounding of the cofactors P 700 and A 1 are present.…”
Section: The Journal Of Physical Chemistry B Pubsacsorg/jpcb Articlesupporting
confidence: 62%
See 1 more Smart Citation
“…Nitroxide radicals, including piperidine nitroxides, have important applications in biophysics as spin labels, especially for EPR distance measurements in biomolecules. The distance measurements, especially few-nm long, require spin labels with long electron spin coherence times T m of the order of a few μs, preferably at temperatures above 80 K. In typical gem -dimethyl nitroxides, the onset of rotation of methyl groups on the EPR time scale at T > 80 K lowers T m significantly. To solve this problem, a number of “methyl-less” spin labels were prepared; for example, Spiro-IA enabled EPR distance measurements in immobilized proteins at room temperature, and diazaadamantane derivative IA-DZD was used to demonstrate the supramolecular approach to EPR distance measurement in proteins up to 150 K (Figure ). …”
Section: Persistent and Stable Monoradicals As Spin Centersmentioning
confidence: 99%
“…Tremendous efforts have been made to probe macromolecules in natural biological systems that can provide insight into their structures and functions. Site-directed spin labeling (SDSL) pulsed electron paramagnetic resonance (EPR) dipolar spectroscopy (PDS), which includes double electron–electron resonance (DEER) and double quantum coherence (DQC), is among the best techniques for accurate measurement of the conformations of flexible regions of biomolecules. The advantages include high sensitivity, wide dynamic range, absolute distance distributions, and minimal structural perturbation from relatively small-size nitroxide spin labels. , The most widely used spin label for SDSL is methane thiosulfonate pyrroline nitroxide (MTSL), which selectively binds to cysteine, that can be introduced at selected locations by mutagenesis to provide doubly labeled proteins. , Using nitroxides, these measurements require cryogenic temperatures because of the dynamic averaging effects associated with methyl group rotation, which shorten the electron spin coherence time ( T m ) between about 80 and 300 K. …”
Section: Introductionmentioning
confidence: 99%